Associação entre aptidão física e conhecimentos nutricionais em adolescentes de ambos os sexos - Tiago Augusto Amaral Matos (2017)
Objective: The objective of this study was to establish a relationship between physical fitness and food nutrition on both genders. Material and methods: The sample of the present study consisted of 116 students, 65 females and 51 males. All students belong to the Basic and Secondary School of Airães located in Felgueiras. The age of the students is between 12 and 17 years old. Fitnessgram was used as a direct method, but the test was used to assess the physical fitness and indirectly a questionnaire was used for physical activity(PA)evaluation. A food knowledge questionnaire (QCNA) was used to evaluate food knowledge. Results: The shuttle test evaluates aerobic fitness and consists of performing the maximum number of laps performed at a distance of 20m at a predetermined pace. In this sense, males adolescents' aerobic fitness (M = 58.64, SD = 18.71) was higher than in females (M = 32.26, SD = 12.25) (p <.001); Regarding nutritional and feeding knowledge, however, correlations with anthropometric measurements were found: more knowledge about food choices was associated with lower BMI values (r = -245, p <.05); (r = .233, p <.05), flexibility on the right (r = .317, p <.01), and left flexibility (r = .306, p <.01); more knowledge about the source of nutrients was associated with more flexibility on the left (r = .226, p <.05), but lower aerobic fitness (r = -209, p <.05); (r = .236, p <.05) and on the left (r = .287, p <.01) were more closely related. Conclusion: The present study doesn't have significant statistical results in those variables studied, in order to establish a positive relationship between dietary knowledge and physical fitness.